Application of copper-doped carbon quantum dots in improving salt tolerance of crop seeds and seedling stage
By combining copper-doped carbon quantum dots with carbon quantum dots, the problem of difficulty in improving salt tolerance in the seeds and seedlings in the prior art is solved, and the growth and yield of crops under salt stress is achieved significantly.
Patent Information
- Application Number
- CN202411980205.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-31
AI Technical Summary
The prior art is difficult to effectively improve the salt tolerance of crops in seeds and seedling stages, resulting in reduced crop growth and yield under salt stress.
Copper-doped carbon quantum dots (CuCDs) are used to prepare copper-doped carbon quantum dots by combining copper elements with carbon quantum dots, which is used to improve salt tolerance in crop seeds and seedlings.
Copper-doped carbon quantum dots significantly improve the germination rate, fresh weight and germination index of crop seeds under salt stress, as well as the fresh weight, chlorophyll content and antioxidant properties of the above-ground and underground areas of the seedling stage.
Smart Images

Figure CN119655010A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of agricultural technology, and more specifically, relates to the application of copper-doped carbon quantum dots in improving the salt tolerance of crop seeds and seedlings. Background Art
[0002] Soil salinization affects arable land in many countries and is one of the important factors limiting crop yields. Salt stress first inhibits seed germination, reduces seed emergence rate in the field, leads to uneven emergence and reduced yield in the later stage. Secondly, after seed emergence, salt stress continues to act, causing plants to be subjected to osmotic stress, ionic stress and oxidative stress during the growth stage. Therefore, it is crucial to improve the salt tolerance of crops at the seed and seedling stage to maintain their healthy vegetative growth.
[0003] At present, the conventional methods to solve soil salt stress mainly include farmland water management, soil improvement, optimization of agronomic measures, breeding and planting of salt-tolerant crops. Although these methods have certain effects, they require a lot of resources and time. For example, salt removal through farmland irrigation water can dilute and remove salt in the soil, but saline-alkali land is mostly in water-scarce areas in my country, consuming the already scarce irrigation water resources; conventional agronomic measures, such as crop rotation or intercropping with some salt-tolerant crops, can reduce the impact of salt on crops, but not all crops are suitable for rotation or intercropping; breeding of salt-tolerant crops requires breeding or genetic engineering technology, which is difficult to complete in a short time. Therefore, there is an urgent need for a new and easy-to-operate technology to alleviate crop salt stress.
[0004] Copper (Cu) is an essential trace element for plant growth. Although plants require relatively little copper, copper plays an important role in many physiological and biochemical processes of plants, especially in enzyme activation, anti-oxidation, disease resistance, and plant growth and development. First, copper is a key component of many enzymes, especially peroxidase, polyphenol oxidase, cytochrome enzyme, and superoxide dismutase, which play a key role in the anti-oxidation process under salt stress; secondly, copper participates in key processes of plant growth such as lignin synthesis, auxin metabolism, photosynthesis, electron transfer, and flowering and fruiting of plants, and plays an important role in plant growth and development.
[0005] As an emerging field in agriculture, nano-agriculture has a high application prospect in improving agricultural production efficiency, reducing environmental pollution, improving crop quality and promoting sustainable agricultural development. For example, Lovely et al. found that nano copper oxide can promote the growth of radish under salt stress (Lovely Mahawar C; Marek Maria Barboricova; et al. Effect of copper oxide and zinc oxide nanoparticles on photosynthesis and physiology of Raphanus sativus L. under salinity stress [J]. Plant Physiology and Biochemistry, 2023, Vol. 206: 108281). However, high concentrations of metal oxides, such as copper oxide nanoparticles, can harm plants, leading to reduced crop growth and yield (Feigl, G. (2023). The impact of copper oxide nanoparticles on plant growth: a comprehensive review. Journal of Plant Interactions, 18 (1). https: / / doi.org / 10.1080 / 17429145.2023.2243098). Therefore, a more biocompatible alternative is needed to reduce the toxicity of nanomaterials while improving the salt tolerance of crops. Carbon quantum dots (CQDs) are a new type of bioluminescent carbon nanomaterials with good biocompatibility, water solubility, and low toxicity. They have great application potential in bioimaging, fluorescence sensing, drug delivery, plant growth, etc. However, there are few studies on copper-doped carbon quantum dots in improving plant growth. Summary of the invention
[0006] The technical problem to be solved by the present invention is to overcome the defects and shortcomings of the prior art and provide an application of copper-doped carbon quantum dots in improving the salt tolerance of crop seeds and seedlings.
[0007] The purpose of the present invention is to provide the application of copper-doped carbon quantum dots in scavenging hydroxyl radicals, superoxide anions and hydrogen peroxide in vitro.
[0008] The purpose of the invention is to provide a method for improving the salt tolerance of crop seeds.
[0009] Another object of the present invention is to provide a method for improving the salt tolerance of crops at the seedling stage.
[0010] The above-mentioned purpose of the present invention is achieved through the following technical solutions:
[0011] The invention provides application of copper-doped carbon quantum dots in improving salt tolerance of crop seeds and seedlings.
[0012] The inventors have found through extensive research that, at the same concentration, the application of copper ions or carbon quantum dots alone has no significant effect on the fresh weight of the aboveground and underground parts under salt stress, indicating that the application of copper ions or carbon quantum dots alone has no significant promoting effect on the growth and development of crops under salt stress. However, the inventors have found that combining copper elements and carbon quantum dots to prepare copper-doped carbon quantum dots has a synergistic effect and can significantly promote the growth and development of crop seeds and seedlings under salt stress.
[0013] Preferably, the improving salt tolerance of crop seeds and seedlings is: improving at least one of the germination rate, fresh weight, germination index and germination potential of crop seeds under salt stress, and improving at least one of the aboveground fresh weight, underground fresh weight, chlorophyll content and antioxidant activity of crop seedlings under salt stress.
[0014] Preferably, the crop is cotton.
[0015] The present invention also provides the use of copper-doped carbon quantum dots in removing hydroxyl radicals, superoxide anions and hydrogen peroxide in vitro.
[0016] The inventors have found through extensive research that the copper-doped carbon quantum dots of the present invention have the ability to scavenge free radicals, superoxide anions and hydrogen peroxide in vitro, and can function as a nano-enzyme.
[0017] Preferably, the copper-doped carbon quantum dots include the following preparation method: copper nitrate, urea, citric acid, and N,N-dimethylformamide are mixed, subjected to solvent thermal reaction, and post-treated to obtain copper-doped carbon quantum dots.
[0018] Furthermore, the temperature of the solvent thermal reaction is 160-200°C.
[0019] Furthermore, the solvent thermal reaction time is 4 to 6 hours.
[0020] Furthermore, the copper nitrate, urea, citric acid, and N,N-dimethylformamide are mixed in a ratio of 0.2-0.4 g: 1-2 g: 0.5-1 g: 10 mL.
[0021] Furthermore, the post-treatment is to centrifuge and take the supernatant to mix with ethanol, and finally take the precipitate and dry it.
[0022] Preferably, the volume ratio of the supernatant to ethanol is 1:1.5-2.5.
[0023] Furthermore, the present invention provides a method for improving the salt tolerance of crop seeds, wherein the crop seeds are immersed in a copper-doped carbon quantum dot solution; wherein the concentration of the copper-doped carbon quantum dot solution is 20 to 50 mg / L.
[0024] Preferably, the mass ratio of the crop seeds to the copper-doped carbon quantum dot solution is 1:4-6.
[0025] Preferably, the concentration of the copper-doped carbon quantum dot solution is 20-26 mg / L.
[0026] Preferably, the soaking time is 7 to 9 hours.
[0027] In addition, the present invention also provides a method for improving the salt tolerance of crops at the seedling stage, wherein a solution containing copper-doped carbon quantum dots is applied to the surface of the crops; wherein the concentration of the copper-doped carbon quantum dots in the solution is 250 to 2000 mg / L.
[0028] Preferably, the concentration of copper-doped carbon quantum dots in the solution is 500-1000 mg / L.
[0029] Preferably, the concentration of copper-doped carbon quantum dots in the solution is 450-550 mg / L.
[0030] Preferably, the solution further contains an organosilicon surfactant.
[0031] Furthermore, the organosilicon surfactant is a polysiloxane polyether surfactant.
[0032] More preferably, the volume concentration of the silicone surfactant in the solution is 0.5‰.
[0033] Compared with the prior art, the present invention has the following beneficial effects:
[0034] The present invention provides an application of copper-doped carbon quantum dots in improving the salt tolerance of crop seeds and seedlings. The present invention has found that after crop seeds are treated with copper-doped carbon quantum dots, the germination rate, germination index and germination potential of seeds under salt stress can be significantly improved; after crop seedlings are treated with copper-doped carbon quantum dots, the above-ground fresh weight and underground fresh weight of crops under salt stress can be significantly improved. In addition, after crop seedlings are treated with copper-doped carbon quantum dots, the chlorophyll content and the antioxidant properties of crops can also be significantly improved.
[0035] In addition, copper-doped carbon quantum dots can be used as seed soaking agents or foliar fertilizers on crops, which can quickly improve the salt tolerance of crops in a short period of time (5 to 7 days). It has low cost and high benefits. Copper-doped carbon quantum dots are harmless to the environment and will not cause potential biosafety issues such as heavy metal accumulation. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 The ultraviolet-visible absorption spectra and fluorescence spectra of the copper-doped carbon quantum dots prepared in Examples 1 to 4 and the carbon quantum dots prepared in Comparative Example 1 are shown. Figure 1 Figure A is the UV-visible absorption spectrum. Figure 1 Figure B is a fluorescence spectrum.
[0037] Figure 2 This is a structural characterization diagram of the copper-doped carbon quantum dots prepared in Example 1. Figure 2 Figure A shows the transmission electron microscope image and lattice diagram of copper-doped carbon quantum dots. Figure 2 Figure B shows the particle size distribution and average particle size. Figure 2 The C diagram in the figure is the potential diagram. Figure 2 Figure D in the figure is the UV-visible absorption spectrum and the best excitation emission fluorescence spectrum. Figure 2 Figure E in the figure is an X-ray diffraction pattern.
[0038] Figure 3 The phenotype diagram and germination rate data statistics of cotton seeds grown under salt stress after copper-doped carbon quantum dots soaking treatment. Figure 3 Figure A is a phenotype diagram of cotton seed germination. Figure 3 Figure B shows the germination rate of cotton seeds. Figure 3 Figure C shows the fresh weight of cotton seeds. Figure 3 Figure D in the figure is the germination index of cotton seeds. Figure 3 Figure E shows the germination potential of cotton seeds.
[0039] Figure 4 The phenotype of cotton seedlings under salt stress and the statistical data of fresh weight of aboveground and underground parts after copper-doped carbon quantum dots were applied. Figure 4 Figure A is the growth phenotype of cotton seedlings. Figure 4 Figure B is a statistical chart of the fresh weight of the aboveground part of cotton after spraying copper-doped carbon quantum dots at the seedling stage. Figure 4 Figure C is a statistical chart of fresh weight of underground parts of cotton after spraying copper-doped carbon quantum dots at the seedling stage.
[0040] Figure 5 The phenotype of cotton seedlings under salt stress and the statistical data of fresh weight of aboveground and underground parts after treatment with copper-doped carbon quantum dots, carbon quantum dots and copper nitrate. Figure 5 Figure A is the growth phenotype of cotton seedlings. Figure 5 Figure B is a statistical chart of the fresh weight of the aboveground part of cotton seedlings. Figure 5 Figure D is a statistical chart of fresh weight of underground parts of cotton seedlings.
[0041] Figure 6 This is a statistical chart of chlorophyll content in cotton seedlings under salt stress after copper-doped carbon quantum dots were applied. Figure 6 Figure A is a statistical chart of chlorophyll a content. Figure 6 Figure B is a statistical chart of chlorophyll b content. Figure 6Figure C is a statistical graph of total chlorophyll content. Figure 6 Figure D is a statistical graph of carotenoid content.
[0042] Figure 7 This is a diagram of chlorophyll fluorescence parameters of cotton seedlings under salt stress after treatment with copper-doped carbon quantum dots.
[0043] Figure 8 This is a statistical chart of the content of hydrogen peroxide and superoxide anion radicals in cotton seedlings under salt stress after treatment with copper-doped carbon quantum dots. Figure 8 Figure A is a statistical chart of hydrogen peroxide content. Figure 8 Figure B is a statistical graph of superoxide anion radical content data.
[0044] Fig. 9 This is a statistical chart of antioxidant enzyme activity data in cotton seedlings under salt stress after copper-doped carbon quantum dots were applied. Fig. 9 Figure A is a statistical diagram of SOD enzyme activity data. Fig. 9 Figure B is a statistical diagram of POD enzyme activity data. Fig. 9 Figure C is a statistical graph of CAT enzyme activity data. DETAILED DESCRIPTION
[0045] The present invention is further described below in conjunction with the accompanying drawings and specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0046] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0047] Example 1
[0048] The preparation method of copper doped carbon quantum dots (Cu doped Carbon quantum dots, hereinafter referred to as CuCDs) is as follows:
[0049] First, 0.2g copper nitrate and 2g urea were dissolved in 10mL N,N-dimethylformamide (DMF), and then 1g citric acid was added. After fully dissolved, the mixture was reacted at 160°C for 6h. After cooling to room temperature, the solution was centrifuged at 12000r / min for 20min to remove the precipitate; the supernatant was mixed with ethanol at a volume ratio of 1:2 and centrifuged at 12000r / min for 10min, and then the precipitate was freeze-dried to obtain CuCDs powder.
[0050] Example 2
[0051] First, 0.2g copper nitrate and 1g urea were dissolved in 10mL N,N-dimethylformamide (DMF), and then 0.5g citric acid was added. After fully dissolved, the mixture was reacted at 160°C for 6h. After cooling to room temperature, the solution was centrifuged at 12000r / min for 20min to remove the precipitate; the supernatant was mixed with ethanol and centrifuged at 12000r / min for 10min, and then the precipitate was freeze-dried to obtain CuCDs powder.
[0052] Example 3
[0053] First, 0.4 g of copper nitrate and 2 g of urea were dissolved in 10 mL of N,N-dimethylformamide (DMF), and then 1 g of citric acid was added. After fully dissolved, the mixture was reacted at 160°C for 6 h. After cooling to room temperature, the solution was centrifuged at 12000 r / min for 20 min to remove the precipitate; the supernatant was mixed with ethanol at a volume ratio of 1:2 and centrifuged at 12000 r / min for 10 min, and then the precipitate was freeze-dried to obtain CuCDs powder.
[0054] Example 4
[0055] First, 0.2g copper nitrate and 1g urea were dissolved in 10mL N,N-dimethylformamide (DMF), and then 0.5g citric acid was added. After fully dissolved, the mixture was reacted at 200℃ for 4h. After cooling to room temperature, the solution was centrifuged at 12000r / min for 20min to remove the precipitate; the supernatant was mixed with ethanol at a volume ratio of 1:2 and centrifuged at 12000r / min for 10min, and then the precipitate was freeze-dried to obtain CuCDs powder.
[0056] Comparative Example 1
[0057] Compared with Example 1, copper nitrate was not added in this comparative example, and other preparation methods and conditions were the same, and carbon quantum dots CDs were finally prepared.
[0058] Experimental Example 1 Material Characterization
[0059] Experimental materials: copper-doped carbon quantum dots (CuCDs) prepared in Examples 1 to 4, and CDs prepared in Comparative Example 1.
[0060] The UV-visible absorption spectra of CuCDs and CDs were obtained by AOE UV-1800PC spectrophotometer. Fluorescence spectra were obtained in a quartz cuvette (10 mm × 10 mm) using a Shimadzu RF-6000 fluorescence spectrophotometer. The potential of CuCDs was measured by Malvern Zetasizer nano ZS. Transmission electron microscopy (TEM) was performed using a FEI Talos F200c TEM at 200 kV. X-ray diffraction (XRD) was performed on a Bruker X-ray diffractometer D8 ADVANCE.
[0061] Figure 1 The UV-visible absorption spectra of the CuCDs prepared in Examples 1 to 4 and the CDs prepared in Comparative Example 1 ( Figure 1 Figure A) and fluorescence spectra ( Figure 1 Figure B in Figure 2), Figure 1 CuCDs-1 represents the CuCDs prepared in Example 1, CuCDs-2 represents the CuCDs prepared in Example 2, CuCDs-3 represents the CuCDs prepared in Example 3, and CuCDs-4 represents the CuCDs prepared in Example 4. Through comprehensive comparison, CuCDs-1 (CuCDs prepared in Example 1) has the highest fluorescence intensity, indicating that the fluorescence efficiency of the copper-doped carbon dots is the highest, so the CuCDs under this synthesis scheme are selected as the subsequent test objects.
[0062] Figure 2 This is a relevant characterization diagram of CuCDs prepared in Example 1, wherein: Figure 2 Figure A shows the transmission microscope imaging of CuCDs and the carbon dot lattice. The results show that CuCDs is a nanomaterial with a uniform distribution and a lattice of 0.24nm. Figure 2 Figure B shows the particle size distribution and average particle size of CuCDs. The particle size of CuCDs is 2.04±0.04nm. Figure 2 Figure C shows that the CuCDs potential was measured at -27.83±0.33mV. Figure 2 Figure D shows the UV-visible absorption spectrum and optimal fluorescence spectrum of CuCDs. Figure 2 Figure E in the figure is the X-ray diffraction analysis (XRD) of CuCDs. The above results show that Example 1 successfully synthesized copper-doped carbon quantum dots with a negative surface potential and a particle size of 2.04 nm.
[0063] Experimental Example 2
[0064] Experimental materials: copper-doped carbon quantum dots (CuCDs) prepared in Example 1.
[0065] The ability of copper-doped carbon nanodots to scavenge reactive oxygen species in vitro was determined by the following specific detection methods:
[0066] Hydrogen peroxide (H 2 O 2 ) content was determined using the "Hydrogen Peroxide Content Determination Kit" (A064-1-1, Nanjing Jiancheng Biological Co., Ltd.). Based on the fact that hydrogen peroxide can react with molybdic acid to form a complex with a characteristic absorption peak at 405 nm, the efficiency of the material in removing hydrogen peroxide can be calculated. The sample was added according to the sample addition process in the kit instructions, and CuCDs (final concentration of 10 mg·L -1 and 50mg·L -1 ) solution, mix well, and measure the absorbance at a wavelength of 405nm and a light path of 1cm.
[0067] Superoxide anion (O 2 · - The in vitro clearance efficiency of ) was determined using a SOD activity assay kit (WST-1, Shanghai Bio-Tech Biotech Co., Ltd.). First, the O generated by the reaction of xanthine and xanthine oxidase was used. 2 · - It reacts with WST-1 to generate a water-soluble dye that can be detected (maximum absorption at 450nm), and the absorbance value is linearly related to the concentration. -1 and 50mg·L -1 ) solution was added to the mixture of xanthine and xanthine oxidase, incubated at 37°C for 30 min, and the absorbance at 450 nm was measured using a microplate reader.
[0068] · OH scavenging capacity determination, specific preparation method: take 3mL of Tris-HCl (0.1mol·L -1 , pH = 4.7), methyl violet (24 μmol·L -1 ), FeSO 4 (1.08mmol·L -1 ), H 2 O 2 (0.1mol·L -1 ) of CuCDs (final concentration was 10 mg·L -1 or 50mg·L -1 ) solution, the above solution without CuCDs was used as standard control, and 3 mL of methyl violet (24 μmol·L -1 ) solution was used as a blank control. Each test tube was placed in a 37°C constant temperature water bath for reaction for 30 min. After the reaction, the absorbance of each tube was measured at 582 nm. The measured data were recorded and the scavenging rate of CuCDs on hydroxyl radicals was calculated according to the following formula:
[0069] CuCDs scavenging rate of hydroxyl radicals (%) = (1-△α582 / △A582)*100
[0070] Where: △α582 is A blank control-A determination
[0071] △A582 is A blank control-A standard control
[0072] The test results are shown in Table 1. It can be seen from Table 1 that the concentration is 10 mg·L -1 and 50mg·L -1 The scavenging rates of CuCDs for hydrogen peroxide, hydroxyl radicals, and superoxide anions were 16.99% and 47.42%, 0.74% and 17.27%, 4.49%, and 93.77%, respectively, indicating that CuCDs can function as a nanoenzyme mimic.
[0073] Table 1. In vitro scavenging of H by Cu-doped carbon nanodots 2 O 2 , ·OH, ·O 2 - Capabilities
[0074] <![CDATA[H 2 THE 2 ]]> OH <![CDATA[O 2 · - ]]> <![CDATA[10mg·L -1 CuCDs]]> 16.99% 0.74% 4.49% <![CDATA[50mg·L -1 CuCDs]]> 47.42% 17.27% 93.77%
[0075] Experimental Example 3
[0076] Experimental materials: copper-doped carbon quantum dots (CuCDs) prepared in Example 1.
[0077] Copper-doped carbon nanodots improve cotton seed germination rate and growth under salt stress
[0078] Cotton (variety: Huamian 3097) seed disinfection, sowing and introduction treatment: The seeds were disinfected with 5% sodium hypochlorite and then rinsed with pure water 3 times. After drying, the CuCDs prepared in Example 1 were prepared into a soaking agent with a mass concentration of 25 mg / L and 50 mg / L with deionized water, and deionized water was used as a control (Control). The seeds were immersed in the above soaking agent at room temperature, the mass ratio of the seeds to the soaking agent was 1:5, and the soaking time was 8h. Two layers of germination paper were laid in the germination box, and 10mL of 200mM NaCl solution was added to each box. The soaked cotton seeds were evenly placed on the germination paper, 30 seeds (5×6) were placed in each culture dish, and 4 groups were repeated. The culture dishes were placed in a culture room with a light of 16h and a dark of 8h for cultivation. The number of seeds germinated each day was counted, and the fresh weight was weighed after 7 days. The germination rate, germination potential and germination index were calculated according to the following formula.
[0079]
[0080] Where n represents the statistical date of germination, and its value is 1-7.
[0081] Figure 3 Figure A shows the germination phenotype of cotton grown for 7 days after 8 hours of CuCDs introduction. It can be seen that the cotton seeds grew better after the introduction of CuCDs, and the cotton at the two concentrations was significantly better than the control treatment. Figure 3 The BE graph in the figure shows the germination rate, fresh weight, germination index and germination potential of the introduced cotton seeds 7 days later. The results show that the germination rate, germination index and germination potential of the seeds introduced by CuCDs are significantly higher than those of the control treatment.
[0082] Experimental Example 4
[0083] Experimental materials: copper-doped carbon quantum dots (CuCDs) prepared in Example 1, CDs prepared in Comparative Example 1, and copper nitrate.
[0084] Experimental method: Cotton (variety: Huamian 3097) seeds were sterilized. After soaking in pure water at 25°C for 3 hours, the seeds were sown in a 10 cm × 10 cm plastic nutrient pot filled with nutrient soil (peat: vermiculite: perlite = 1:1:1). When the cotyledons of the seedlings were fully expanded, the seedlings were transferred to a 5L black plastic square pot filled with 1 / 2 Hoagland nutrient solution (refer to the existing conventional formula, self-prepared). The seedlings were kept at a temperature of 28°C / 18°C (day / night), a 14h light cycle, and 200μmol m -2 ·s -1 of light intensity and 70% to 75% humidity. When the seedlings grow to the second true leaf fully expanded, the test treatment is carried out. First, the optimal application concentration is screened, and deionized water is used to prepare CuCDs solutions with concentrations of 250mg / L, 500mg / L, 1000mg / L, and 2000mg / L. The control group (Control) is deionized water, and the organosilicon surfactant Silwet L-77 is added with a final volume concentration of 0.5‰. After mixing, it is sprayed on the cotton leaves. Dark adaptation in weak light for 3 hours, and then the cotton seedlings are placed in 1 / 2 Hoagland nutrient solution with a concentration of 200mM NaCl (refer to the existing conventional formula, self-prepared) and cultured in a culture room. After 5 days, the phenotype of the cotton seedlings is observed and the fresh weight of the aboveground and underground parts of the cotton is calculated.
[0085] Figure 4 The results show that the phenotype, fresh weight of aboveground and underground parts of cotton under salt stress after treatment with different concentrations of CuCDs solution. The results show that spraying with CuCDs solution can improve the phenotype, fresh weight of aboveground parts and fresh weight of underground parts of cotton under salt stress. Among them, the application of 500mg / L and 1000mg / L CuCDs can significantly improve the phenotype and biomass of cotton under salt stress, indicating that CuCDs can improve the salt tolerance of cotton seedlings.
[0086] Figure 5 For cotton, the concentration of CuCDs, CDs and Cu was 500 mg / L. 2+ After the solution (copper ion concentration in copper nitrate solution is 500 mg / L) was treated according to the above method, the phenotype, fresh weight of aboveground and underground parts of cotton under salt stress were measured. The results showed that compared with the control group, CDs treatment improved the salt tolerance of cotton but there was no significant difference, while the biomass of cotton treated with CuCDs under salt stress increased significantly, and was better than CDs and Cu alone at the same concentration. 2+ This indicates that copper-doped carbon dots can improve the salt tolerance of cotton seedlings, which is comparable to the single CDs and Cu 2+ Compared with the above, it has a synergistic effect.
[0087] Experimental Example 5
[0088] Experimental materials: cotton leaves treated with 500 mg / L CuCDs solution and deionized water after being treated according to the experimental method in Experimental Example 4.
[0089] Chlorophyll content detection
[0090] 0.1 g of fresh cotton leaves treated with 500 mg / L CuCDs solution and deionized water and placed under salt stress for 5 days in Example 4 were weighed, cut into small pieces and placed in a 15 mL centrifuge tube, 10 mL of a 1:1 (v:v) mixture of anhydrous ethanol and acetone was added to the centrifuge tube, and placed in the dark for 24 hours to fully extract chlorophyll. The absorbance of the extract at 440 nm, 644 nm and 662 nm was measured using an ELISA instrument and calculated according to the following formula:
[0091] Chlorophyll a concentration (mg / L, Ca) = 9.784*A662-0.99*A644
[0092] Chlorophyll b concentration (mg / L, Cb) = 21.426*A644-4.65*A662
[0093] Total chlorophyll concentration (mg / L) = chlorophyll a concentration + chlorophyll b concentration
[0094] Carotenoid concentration (mg / L) = 4.695*A440-0.268*(Ca+Cb)
[0095] Pigment content (mg / g) = [pigment concentration (mg / L)*total amount of extract (mL)] / [leaf weight (g)*1 000], wherein the pigment is chlorophyll a, chlorophyll b or carotenoid.
[0096] Measurement results Figure 6As shown in the results, application of CuCDs to cotton under salt stress can effectively maintain the chlorophyll content in leaves, and the contents of chlorophyll a, chlorophyll b, total chlorophyll and carotenoids were significantly increased compared with the control group.
[0097] Experimental Example 6
[0098] Experimental materials: cotton leaves treated with 500 mg / L CuCDs solution and deionized water after being treated according to the experimental method in Experimental Example 4.
[0099] Using the chlorophyll fluorescence imaging system (IMAGING-PAM, WALZ, Germany), the cotton seedlings of each treatment group (500 mg / L CuCDs solution treatment group and deionized water treatment group) in Experimental Example 4 were subjected to salt stress for 5 days to analyze the chlorophyll fluorescence parameters by fluorescence imaging. The plants were placed in the dark for at least 30 minutes before the measurement. The setting of the pulse modulation measurement light intensity was adjusted according to the real-time fluorescence value (Ft) of each region of interest to ensure that the Ft value was within the range of 0.01 to 0.02, at which time the instrument reached the optimal measurement state. The measurement parameters were: maximum photochemical efficiency (Fv / Fm), non-actinic fluorescence quenching (NPQ), actinic fluorescence quenching (qL) and actual photosynthetic quantum yield (Y(II)) under PSII light.
[0100] Figure 7 The results showed that under salt stress, the Fv / Fm and Y(II) of cotton in the CuCDs group were significantly increased, while NPQ and qL were increased but without significant differences. This indicates that the application of CuCDs to cotton under salt stress has a significant effect on improving the photosynthetic efficiency of chlorophyll.
[0101] Experimental Example 7
[0102] Experimental materials: cotton leaves and roots treated with 500 mg / L CuCDs solution and deionized water after treatment according to the experimental method in Experimental Example 4.
[0103] H 2 O 2 The content was determined using the "Hydrogen Peroxide Content Determination Kit" (A064-1-1, Nanjing Jiancheng Biological Co., Ltd.), and the operation was performed according to the instructions. Accurately weigh 0.1 g of cotton leaf and root samples treated with 500 mg / L CuCDs solution and deionized water and under salt stress for 5 days in Example 4, add 1 mL of 0.05 mol / L sodium phosphate buffer (pH = 7.5), grind with a grinder for 120 seconds (65 Hz), then centrifuge at 12000 g, 4 ° C for 20 minutes, and take the supernatant for standby use. Add the sample according to the sample addition process in the instructions, mix well, and measure the absorbance value at a wavelength of 405 nm, an optical path of 1 cm, and zero with deionized water.
[0104] O 2 ·- The content was determined using a superoxide anion content detection kit (Solarbio, China) according to the instructions. Weigh 0.1 g of cotton leaf and root samples treated with 500 mg / L CuCDs solution and deionized water and under salt stress for 5 days in Example 4 and add 1 mL of the extract in the kit. Grind with an ice bath grinder for 180 sec (65 Hz) at 12000 r / min. -1 , centrifuge at 4°C for 20 min, take the supernatant for later use. Add samples according to the sample addition process in the instruction manual, adjust to zero with distilled water, and measure the absorbance of the sample at 530 nm using a spectrophotometer.
[0105] Figure 8 The results showed that the application of CuCDs could significantly reduce H 2 O 2 and O 2 ·- The content of CuCDs in this embodiment of the present invention shows that the CuCDs prepared in this embodiment of the present invention have good antioxidant properties and can remove the excessive H produced by cotton under salt stress. 2 O 2 and superoxide anion radicals, which further promoted the growth of cotton under salt stress and maintained the homeostasis of active oxygen in cotton, thereby alleviating the salt stress of cotton.
[0106] Experimental Example 8
[0107] 0.1 g of fresh cotton leaf and root samples treated with 500 mg / L CuCDs solution and deionized water and under salt stress for 5 days in Example 4 were weighed, 1 mL of 0.05 mol / L sodium phosphate buffer (pH = 7.5) was added, and the leaves were ground in an ice bath using a grinder (65 Hz) for 120 sec and then spun at 12000 r / min. -1 , centrifuge at 4°C for 20 min, and the supernatant is the enzyme extract.
[0108] Superoxide dismutase (SOD) assay: Superoxide dismutase (SOD) assay was performed as described by Wang Xuekui (2006). 1.5 mL 0.05 mol / L PBS, 0.3 mL 0.13 mol / L methionine solution, 0.3 mL 0.75 mmol / L NBT solution, and 0.3 mL EDTA-Na 2Solution, 0.3mL 0.02mmol / L riboflavin solution, add 0.05mL enzyme extract (the light control tube and dark control tube use sodium phosphate buffer instead of enzyme solution), and finally add 0.25mL distilled water to make the total volume 3mL. After mixing, place the dark control tube in the dark, and react the other tubes under 4000lx sunlight for 20min. Measure the absorbance of each tube at 560nm. Calculate SOD activity according to the following formula:
[0109] Total SOD activity (U / g) = (ALC-AE)*V / (0.5*(ALC-ADC*W*VT)
[0110] Wherein: ALC is the absorbance of the light control tube; ADC is the absorbance of the dark control tube; AE is the absorbance of the sample tube; V is the total volume of the sample solution (mL); VT is the amount of sample used during the measurement (mL); W is the fresh weight of the sample (g).
[0111] Peroxidase (POD) assay:
[0112] Prepare the reaction mixture: Take 200 mL of sodium phosphate buffer (PBS, 0.2 M, PH = 6), add 0.076 mL of stock solution of guaiacol (2-methoxyphenol), heat and stir to dissolve, and after cooling, add 0.112 mL of 30% H 2 O 2 . Enzyme activity determination: Take 3mL of the above reaction mixture, add 50μL of enzyme extract, mix well, and use PBS as a control to adjust the absorbance value of the mixture at 470nm. Measure for a total of 180sec, read once every 30sec, and take an increase of 0.01 in absorbance per minute as 1 enzyme activity unit (U). Calculate peroxidase activity according to the following formula:
[0113] POD activity (U / g·min)=(ΔA470*V) / (W*VT*T*0.01)
[0114] Where: △A470 is the change in absorbance during the reaction time; W is the fresh weight of the sample (g); T is the reaction time; V is the volume of the enzyme solution used during the determination (mL); VT is the total volume of the extracted enzyme solution (mL).
[0115] Catalase (CAT) assay: Prepare the reaction mixture: Take 200 mL of sodium phosphate buffer (0.15 M, pH = 7), add 0.3092 ml of 30% H 2 O 2The original solution was shaken. Enzyme activity determination: Take 3mL of the above reaction mixture, add 20μL of enzyme extract, adjust to zero with buffer as the control, and measure the absorbance of the mixture at 240nm. The total measurement was 180sec, and the reading was taken every 30sec. The decrease of 0.01 in absorbance value per minute was 1 enzyme activity unit (U). Calculate CAT activity according to the following formula:
[0116] CAT activity (U / g·min) = (ΔA240*V) / (W*VT*T*0.01)
[0117] Where: △A240 is the change in absorbance during the reaction time; W is the fresh weight of the sample (g); T is the reaction time; V is the volume of the enzyme solution used during the determination (mL); VT is the total volume of the extracted enzyme solution (mL).
[0118] Fig. 9 The results are respectively the results of the SOD, POD and CAT enzyme activity determination of the aboveground and underground parts of cotton after 5 days of salt stress. The results show that the application of CuCDs prepared in the embodiment of the present invention can significantly improve the POD and CAT activities of the aboveground part of cotton under salt stress, and there is no significant difference in the underground part. However, the application of CuCDs did not improve the SOD activity of cotton under salt stress, which may be due to the strong O 2 · - It has the ability to clear bacteria and replaces the SOD enzyme in cotton.
[0119] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. Application of copper-doped carbon quantum dots in improving salt tolerance of crop seeds and seedlings.
2. The use according to claim 1, characterized in that: The crop is cotton.
3. Application of copper-doped carbon quantum dots in scavenging hydroxyl radicals, superoxide anions and hydrogen peroxide in vitro.
4. The use according to claim 1 or 3, characterized in that: The copper-doped carbon quantum dots include the following preparation method: copper nitrate, urea, citric acid, and N,N-dimethylformamide are mixed, subjected to solvent thermal reaction, and post-treated to obtain the copper-doped carbon quantum dots.
5. The application according to claim 4, characterized in that: The temperature of the solvent thermal reaction is 160-200°C.
6. The use according to claim 4, characterized in that: The solvent thermal reaction time is 4 to 6 hours.
7. The use according to claim 4, characterized in that: The copper nitrate, urea, citric acid, and N,N-dimethylformamide are mixed in a ratio of 0.2-0.4 g: 1-2 g: 0.5-1 g: 10 mL.
8. A method for improving the salt tolerance of crop seeds, characterized in that: The crop seeds are soaked in a copper-doped carbon quantum dot solution; wherein the concentration of the copper-doped carbon quantum dot solution is 20 to 50 mg / L.
9. The method according to claim 8, characterized in that: The mass ratio of the crop seeds to the copper-doped carbon quantum dot solution is 1:4-6.
10. A method for improving the salt tolerance of crops at the seedling stage, characterized in that: A solution containing copper-doped carbon quantum dots is applied to the surface of crops; wherein the concentration of the copper-doped carbon quantum dots in the solution is 250-2000 mg / L.
Citation Information
Patent Citations
Application of metal doped carbon dots
CN110327980A
Corn multi-copper oxidase coding gene ZmDEK559-2 and application thereof
CN112063597A
Mimic enzyme material copper-doped carbon quantum dot taking mushroom as carbon source as well as preparation method and application of mimic enzyme material copper-doped carbon quantum dot
CN114958359A
Application of licorice-wolfberry-based carbon quantum dots in improvement of germination rate of crop seeds
CN118140941A
Engineered vesicle as well as preparation method and application thereof
CN118811801A